Listening to Ayahuasca : new hope for depression, addiction, PTSD, and anxiety - Harris, Rachel, 1946- (New World Library, 2017)
"When National Geographic Adventure published an article in 2006 about the powerful antidepressant effects of ayahuasca, the piece received a phenomenal reader response. That article struck a chord with psychotherapist Rachel Harris, who had encountered many clients unresponsive to traditional therapy and antidepressant protocols. Used for more than 8,000 years in the Amazon rainforest, ayahuasca is a powerful - and illegal - psychedelic that has distressing gastrointestinal side effects. Yet Harris found many willing to try it, so deep was their suffering. Harris here shares her original research (the largest study of ayahuasca use in North America) into its effects on depression, anxiety, and PTSD, along with her own personal experiences. By detailing ayahuasca's risks and benefits, she aims to help those driven to investigate ayahuasca to do so safely and to give their psychological caregivers a template for transformative caring and healing" Provided by publisher